Discricionariedade administrativa na definição de metas e métricas de qualidade do serviço de telefonia - Barros, Ricardo Palazzo de Almeida (2010)
We present a brief historical background of the administrative discretion, from its beginning until its insertion at the modern State, under the rule of law. Afterwards, we will discuss the administrative function in accordance with constitutional principles and its system. We examine the doctrine of Brazilian and foreign jurists in search of different ways to understand the administrative discretion. In view of Brazilian law, we visit the competence to use such discretion. We expose two different and opposite doctrines regarding the extension and depth admitted to issue regulatory rules by the administrator under the Brazilian law. We analyze the concepts of quality and its various aspects. Based on the doctrinaire lessons, we observe the use of discretion by ANATEL (Telecommunication Agency) at the definition of quality standards and measurement criteria related to fixed and mobile telephone